ANALISIS METODE HYBRID SAW – TOPSIS DALAM SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PENERIMAAN KREDIT - I Putu Eka Sudarsana; Ni Wayan Noviana Safitri (JURNAL AKADEMISI VOKASI, 2023)
The purpose of this study is to evaluate how well the hybrid decision support system approach evaluates and suggests business financing. Using five criteria—guarantee, income, loan application form (FPP), business establishment permit (SIUP), and guarantee tax—the hybrid technique combines the SAW and TOPSIS approaches. Testing is done on the methods in order to undertake method performance analysis. This seeks to determine the hybrid method's degree of assessment accuracy. The accuracy of debtor rankings is tested using the mean average precision (MAP) technique in this testing procedure. applying the top 10 ranking data, the mean average precision technique was used to test the SAW-TOPSIS method's performance analysis. The results demonstrated that the method had extremely good accuracy, with a value of 83.7%, when applying the test results. The results of the MAP-based data collection method can be analyzed using the hybrid SAW-TOPSIS method, and the data analysis for the hitungan can be further developed by combining more data and analyzing it using more data collection techniques to obtain different results.